Assessment of the peste des petits ruminants (ppr) attenuated virus produced by inoculating vero cell line at different stages of cell growth - El-Dakhly A.T (Egyptian Society for Animal Management, 2016)
This work presents cultural characterization of Peste Des Petites Ruminants (PPR) virus in VERO-culture. The VERO cells are currently considered as an acceptable cell substrate to produce a wide range of viruses. This study evaluates the best time for inoculation of PPR virus on VERO cell cultures; the study proved that the optimum time was 24 hours after subculture of VERO cell line using MOI 2: 1. It was also found that the best time of harvstation of virus fluid of PPR was 9th day post inoculation to reach the best titre 6 log10 TCID50 /ml.